Numerical solutions of the coupled Burgers' equation by the Galerkin quadratic B‐spline finite element method. (25th April 2013) - Kutluay, S.; Ucar, Y.
<x xml:space="preserve">Abstract</x> In this paper, a coupled Burgers' equation has been numerically solved by a Galerkin quadratic B‐spline FEM. The performance of the method has been examined on three test problems. Results obtained by the method have been compared with known exact solution and other numerical results in the literature. A Fourier stability analysis of the method is also investigated. Copyright © 2013 John Wiley & Sons, Ltd.